REPUTATION COMPONENT OF SUSTAINABILITY AND COMPETITIVENESS OF AN AGRARIAN ENTERPRISE - ZAMLYNSKYI, Viktor; CAMARA, Balla Moussa; BLYZNYUK, Tetyana (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Business reputation is one of the key intangible assets of the enterprise, which ensures competitiveness and long-term stability. In the agricultural sector, reputation plays a special role due to the high dependence on the trust of consumers, partners and suppliers in connection with the need for food security conditions to provide processing enterprises with high-quality raw materials and food products for the population in the local and global environment. It is substantiated that the formation of competitiveness of agrarian business takes place with the help of such factors as product quality, ecological production, innovativeness and sustainability of business, as well as effective communication with the market, which requires an appropriate reputational strategy that will ensure an acceptable level of responsibility for product quality standards, social and ecological aspects of production. Accounting and analytical assessment of business reputation is a difficult task due to its intangible nature, therefore we have proposed methods that allow us to evaluate and take into account reputation as an intangible asset, which contain qualitative and quantitative indicators, such as financial stability, feedback from partners and consumers, indicators of sustainable development. Proposals for the formation of influencing factors, evaluation and accounting of intangible assets in the agricultural sector will allow agricultural enterprises to develop a unique competitive strategy, overcome difficulties in the evaluation and reflection on the balance sheet of intangible assets, to which reputation belongs. Aspects of business reputation in the agrarian sector have been studied and proposals have been made for developing criteria for evaluating the reputation of agrarian enterprises, taking into account their socio-economic and environmental impact, which will allow objective measurement of reputation in dynamics. In the conditions of martial law, the search for acceptable and not too expensive innovative technologies, the active use of business social responsibility strategies, maximum transparency and ethics in interaction with partners and consumers, compliance with international standards of quality and sustainable development, which during the globalization process promotes integration with international markets, compliance with global product quality standards and resource management. Production and maintenance of reputable content, evaluation and analysis of ranking based on the examples of the experience of the leading enterprises reflected in our research will help to increase competitiveness and strengthen positions in domestic and foreign markets.